Assessment of the reproductive parameters, laparoscopic oocyte recovery and the first embryos produced in vitro from endangered Caninde goats (Capra hircus) - Souza-Fabjan, Joanna M. G.; Pereira, Alexsandra F.; Melo, Carlos H. S.; Sanchez, Deisy J. D.; Oba, Eunice [UNESP]; Mermillod, Pascal; Melo, Luciana M.; Teixeira, Darcio I. A.; Freitas, Vicente J. F. (Inst Animal Reproduction Food Research, 2013)
The Caninde breed of goats (Capra hircus) is currently endangered. The aims of this study were to characterize the estrus behavior, ovulatory responses and progesterone profiles, and to evaluate the in vitro embryo production (IVP) in this breed. In Experiment 1, ten nulliparous and seven pluriparous females received medroxyprogesterone acetate (MAP)-containing sponges (60 mg) plus 75 mu g D-cloprostenol for estrus synchronization and their reproductive parameters were evaluated. In Experiment 2, oocytes obtained by laparascopy from hormonally stimulated females (n = 15) were used for IVP. There was no difference (p > 0.05) between nulliparous and pluriparous goats in terms of estrus response (40.0% us. 85.7%), time from progestagen sponge removal to the onset of estrus (62.0 +/- 15.5 vs. 50.7 +/- 19.2 h; mean +/- SEM), duration of estrus (25.0 +/- 16.1 vs. 30.0 +/- 15.1 h), percentage of ovulating animals (60.0% vs. 85.7%), number of ovulations (1.2 +/- 0.4 vs. 1.3 +/- 0.8), and diameter of the preovulatory follicle (5.8 +/- 0.5 vs. 6.1 +/- 0.3 mm). Progesterone concentrations were also similar (p > 0.05) in both groups. During laparoscopic recovery, there were average 12.2 aspirated follicles and 9.1 oocytes per goat, resulting in a high recovery rate (74.3%, 182/245). A total of 78 embryos were produced (51.0%). The mean number of cells in the blastocysts at day 7 of in vitro culture was 170.3 +/- 12.5. In conclusion, nulliparous and pluriparous Caninde goats exhibited similar reproductive profiles. It was possible to produce embryos in vitro, allowing the instigation of an embryo bank for preservation of this breed. (C) 2013 Society for Biology of Reproduction & the Institute of Animal Reproduction and Food Research of Polish Academy of Sciences in Olsztyn. Published by Elsevier Urban & Partner Sp. z o.o. All rights reserved.
Keywords: Goat; Estrus; Ovulation; Oocyte recovery; IVP; Conservation